Second Harmonic Generation Properties in Chiral Sarcomeres of Drosophila Larval Muscles - Karunendiran, Abiramy; Mirsanaye, Kamdin; Stewart, Bryan A.; Barzda, Virginijus (Frontiers in Physics, 2022)
Polarimetric second harmonic generation (SHG) microscopy is a label-free ultrastructural imaging technique that is applied to study molecular organization in striated muscle structure. Wild type OreR and UNC45 knockdown Drosophila melanogaster somatic larva body wall muscles are used to elucidate the influence of myosin organization on SHG imaging response. Structural changes due to varying myosin content are studied with linear polarization-in polarization-out (PIPO) SHG microscopy. PIPO SHG microscopy revealed changes in the striated pattern of somatic muscles and a reduced signal intensity correlated with reduced order of myosin filaments. The achiral and chiral susceptibility component ratios R- and C-ratios, respectively, were deduced. R-ratio values were higher in the UNC45 knockdown larva mutant compared to control, suggesting that in addition to myosin, another protein structure provide basis for a second harmonic response. The SHG active protein structure is located in the region of isotropic bands of the striated muscles. The measured C-ratio from the muscle fibers appeared to be small. Nonetheless, the wide distribution of C-ratio values of myosin filaments could be observed in the wild-type OreR muscles. Overall, this technique provides insight on how second harmonic properties change with myosin filament structure.